A new species of Leberis Smirnov, 1989 (Cladocera: Chydoridae) from Colombia - Kotov, Alexey A.; Fuentes-Reinés, Juan M. (Zootaxa, 2015)
A new species of Leberis Smirnov 1989 (Cladocera: Chydoridae) is described based on the material from Ciénaga El Convento (Atlántico Department), Ciénaga Grande de Santa Marta (Magdalena Department), and Laguna Navío Quebrado (La Guajira Department), Colombia. In the Neotropics, Leberis colombiensis sp. nov. could be confused with L. davidi Richard, 1985. But the former differs from the latter in: (1) smaller size; (2) smaller post-pore distance; (3) gonopore region on male postabdomen un-inflated, not overhanging base of postabdominal claw; (4) shorter postanal portion of male postabdomen. Diversity of the genus worldwide is underestimated yet. We believe that more species of Leberis will be described in the future, i.e. after molecular genetic studies.